Analisis Perbedaan Return Saham Sebelum dan Sesudah Pengumuman Right Issue di Bursa Efek Indonesia Tahun 2010-2013 - Rizaldi, Yendri - (Pendidikan Ekonomi, 2014)
The purpose of this study was to analyze the presence of differences in abnormal returns before and after the announcement of the rights issue. This study is event study, using secondary data with the study period of 5 days, 4 days, 3 days, 2 days and 1 day before and after the announcement of the rights issue. A total of 45 companies listed on the Indonesian Stock Exchange in 2010 until 2013 were sampled using a purposive sampling method, which consists of 12 samples to share good news and 33 samples to share bad news. The data used in this study include daily stock closing prices, Composite Stock Price Index (CSPI). The data analysis technique used is, paired sample t-test and independent sample t-test, because the research data were normally distributed. From the research that has been carried out, showing that there is a significant difference in abnormal return on the observation period of 5 days, 4 days, 3 days, 2 days, 1 day before and after the announcement of the rights issue on a group of stocks good news and bad news. Meanwhile, after the announcement of the share issue rught good news is no different than after the announcement of the rights issue shares bad news. So it can be concluded that (1) there is a significant difference in abnormal return for stocks of good news and bad news surrounding the announcement day. This means that the rights issue announcement contains information that is very meaningful. (2) There is no significant difference after the announcement of the rights issue to share good news or bad news, it shows that the announcement of the rights issue does not have significant information content of the reaction of investors. Based on these results, the investor should pay attention and take advantage of each signal is conveyed through the announcement of the rights issue in making investment decisions.